CONSTRUCTION ORGANIZATIONAL CULTURE IN GENDER PESANTREN THROUGH KIAI’S TRANSFORMATIONAL LEADERSHIP - Umiarso Umiarso; Abd. Muhith (Akademika : Jurnal Pemikiran Islam, 2019)
Through transformational leadership, pesantren are able to make institutional changes to achieve success. Because this leadership style can build a strong organizational culture for the effectiveness of Islamic education in pesantren. Therefore, KHMA in PNIA is very effective in carrying out the construction of pesantren culture and shapes the behavior of all pesantren human resources. Therefore, this research uses a qualitative approach with a phenomenological type; which aims to identify and analyze the kiai's transformational leadership style in building an organizational culture in pesantren. The theoretical framework used to analyze the dynamics of the kiai's leadership is the paradigm of Bass & Riggio. He divided the four dimensions of transformational leadership, i.e: idealized influence, inspirational motivation, intellectual motivation, and individual consideration. This research found KHMA constructs pesantren culture by taking from the thoughts of ulama' salaf which are contained in the book of salaf -which is commonly called Kitab Kuning. On the one hand, the effectiveness of KHMA's self-leadership in PNIA is also inseparable from the normative doctrinal values of Islam, so that the kiai's leadership style is based on Islamic values. The implication is that the construction of organizational culture ranging from a philosophical framework to the practical values of pesantren needs to be bound by the basis of social-religious transformation. Keywords: Transformational Leadership, Kiai, and Organizational culture